PENINGKATAN KUALITAS PROD UK KERAJINAN BERBAHAN BAKU SERAT ALAMI MELALUI INOVASI DESAIN - Suharto, Suharto (Universitas Negeri Yogyakarta, 2005)
There was guiding program on handicraft industry for craftsmen at Penguin, Kulonprogo Regency. The goal of the elucidation of handicraft development was to increase the quality of handicraft design in order to make it more competitive in the market. The guiding program aimed to de velop the craftsmen's knowledge and skill to be able to create their own de sign. This would make them not rely only on customers who had the design. The guiding program also gave insight of how to manage the handicraft in dustry that covered human resources management, production, product mar keting, and the other process in the industry.The guiding program used lecturing method given to the craftsmenPengasih pendopo (the audience hall of the sub-district) which was attended by the sub-district officials and 19 craftsmen from four types of the handi craft industry: rope-craft, coconut-fiber-craft, bamboo-craft, and wood carv ing. After lecturing, tutors team gave design models of handicraft to add de sign varieties in order to train the craftsmen in creativity. This plain training would be evaluated and criticized by the tutors to make it a continued pro cess.The product of handicrafts involved: crafts made of coconut-fiber such asdoormat and brooms; crafts made of rope used agel, rami, mendong, and enceng gondok material: bags and cases; crafts made of bamboo such as furniture and bird- cages; and wood carving. The entire product was resulted from mariual work with plain design. To product handicrafts is a side job for the men whose main jobs are farmers. They use their free time while waiting harvest for making the handicrafts.Key word: the development of handicrafts design